A green route for preparation of low surface area SiO2 microspheres from wheat straw ash with activated carbon and NPK compound fertilizer as by-products1. Issue 98 (23rd October 2015) - Cui, Jinlong; Cui, Liying; Cheng, Fupeng; Liu, Lingjuan; Sun, Hongliang; Li, Song; Wen, Zhongsheng; Sun, Juncai
<x xml:space="preserve">Abstract</x> Every components of the wheat straw ash and all the chemicals involved in this route have been effectively used.